Development of semi-synthetic microbial consortia of Streptomyces coelicolor for increased production of biodiesel (fatty acid methyl esters). (1st November 2015) - Bhatia, Shashi Kant; Yi, Da-Hye; Kim, Yong-Hyun; Kim, Hyun-Joong; Seo, Hyung-Min; Lee, Ju-Hee; Kim, Jung-Ho; Jeon, Jong-Min; Jang, Kyoung-Soon; Kim, Yun-Gon; Yang, Yung-Hun
Graphical abstract: Highlights: S. coelicolor accumulate fatty acids up to 3.2% of biomass. S. coelicolor Δ manA : R. eutropha produce 124% more fatty acids as compared to S. coelicolor . The CN value of biodiesel produced by consortia is 64.56. Oxidation stability of biodiesel is 75.98 h. Abstract: Biodiesel, an alternative to petroleum oil has gained significant attention from the research community because of its high energy content and good compatibility with existing engine systems. It can be produced from many different sources, such as animals, plants, and microbes. In this study, we demonstrated the overproduction of fatty acid methyl esters (FAMEs) using a synthetic consortium of manA mutant Streptomyces coelicolor with Ralstonia eutropha . The synthetic consortium of S. coelicolor Δ manA : R. eutropha produced 114 mg/L fatty acids, which is 124% higher than the amount produced using S. coelicolor alone. Overall, the fatty acids produced by the consortia S. coelicolor Δ manA : R. eutropha were composed of medium chain fatty acid (MCFA): long chain fatty acid (LCFA): very long chain fatty acid (VLCFA) in 8.75: 91.0: 0.25 proportion, and contained 75% saturated and 25% unsaturated fatty acids, which resulted in FAMEs with better cetane number (65) and oxidation stability (76 h) than the fatty acids produced by one strain alone. Nile red staining and subsequent fluorescence spectroscopy revealed S. coelicolor Δ manA as good candidate for triacylglycerol (TAG) accumulation. Phospholipid-derived fatty acids (PLFA) analysis of consortia shows that S. coelicolor Δ manA and R. eutropha synergistically support each other's growth. The results suggest that the synthetic consortium provides an approach for biodiesel production along with improved quality.